Critical Digital Literacy: EFL Students’ Ability to Evaluate Online Sources - Sary Silvhiany; Siti Huzaifah; Ismet Ismet (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
The advancement of Internet-based technologies and the new media ecology have contributed to the increased reliance on online sources in both the academic and the non-academic contexts. This study investigated how students evaluated the credibility of online information and the bias that might have influenced the content of the information. 152 EFL students responded to the online critical literacy assessment, which consisted of six tasks: evaluating the credibility of visual information, evaluating WhatsApp message, comparing and evaluating websites, distinguishing between news and sponsored content, evaluating the credibility of claim in a YouTube video, and evaluating an Instagram post. The results of the study showed that the students were easily deceived by the online information they read from various online media. They particularly struggled to detect the unsubstantiated claims from the YouTube video. Despite being a generation Z who frequently used social media and various online sources in their daily lives, the students could not critically evaluate the claims posted on these platforms. Implications of this study include the need to incorporate critical digital literacy in the language skill courses and deliberate exposure to strategies in evaluating online sources.